The Strategy of Tadzkirah in Implementing Characters at MAN Insan Cendekia Sambas - Liliana; Purniadi Putra; Aslan (Tarbiyah Departement collaboration with AMCA, 2021)
This Artiel examines the tadzkirah strategy in instilling the character values ​​of students in MAN insan chili sambas, West Kalimantan. This study is more focused on aspects (1) Learning Planning for Akidah Akhlak in Instilling Student Character in MAN Insan Cendekia Sambas, (2) how is the tadzkirah strategy in instilling character in students at MAN Insan Cendekia Sambas. This research uses a qualitative approach. The results of this study indicate that (1) to formulate learning objectives, we should pay attention to the material to be delivered, the student's health condition, their abilities and the supporting facilities to be used. The learning materials chosen should be tailored to the needs of students, the list of materials listed in the syllabus and the material has something to do with moral development. Considering the selection of teaching methods, the goals to be achieved, the conditions of students and teachers, and the environment around the school, collaboration methods such as (lecture methods, stories, discussions, exercises, assignments, demonstrations), group work and exemplary, (2) as for strategies tadzkirah in planning akidah akhlak learning in instilling student character values ​​in MAN Insan Cendekia Sambas, is to pray before the learning process, preparation of classroom situations in general, preparation of conditions for students who will receive material, preparation of material to be delivered, preparation of methods, media and assessment .Religious and sociological approaches. While the effective media used in learning akidah akhlak to instill the character values ​​of students in MAN Insan Cendekia Sambas are the facilities of the mosque and the school environment.